ASSISTANCE OF LIVING PHARMACY CULTIVATION AS AN EFFORT TO UTILIZE EMPTY YARD LAND IN TINGGAR BUNTUT VILLAGE, MOJOKERTO DISTRICT - Moch Nurcholis Majid; Rinda Rinda; Aida Fitrianah Zen (PANDAWA : Jurnal Pengabdian kepada Masyarakat, 2023)
The empowerment of housewives in Tinggar Buntut Village in planting and utilizing TOGA can be used to support the empowerment of PKK mothers by utilizing the existing environment in the area. TOGA is a houseplant that has medicinal properties. The use of TOGA apart from being a medicine can also be used for: (1) family nutrition (papaya, cucumber, spinach), (2) cooking spices or spices (turmeric, kencur, ginger, lemongrass), (3) adding beauty (rose , jasmine, sunflower). The gotong royong activity was held on Saturday 04 March 2023 in the yard of the Tinggar Buntut village hall, Bangsal District, Mojokerto district. Activities carried out with the lecture method in the form of counseling and demonstrations. Lecture method (counseling) to explain the efficacy of TOGA scientifically, cultivation of Family Medicinal Plants (TOGA), and processing of TOGA. Demonstration method of cultivating Medicinal Plants of the Family (TOGA). Therefore it is necessary to conduct training on the efficacy of TOGA scientifically. Communities who already have knowledge about the efficacy of TOGA and know how to process it can cultivate medicinal plants individually and use them so that the principle of independence in family medicine will be realized. Apart from that, it can also be developed into small and medium enterprises in the herbal medicine sector, which can then be distributed to the community